Tunnel Boring Machine Design and Reliability Parameters of a Dynamic Rock-Indentor System - Malindzakova, Marcela; Futo, Jozef (Communications - Scientific letters of the University of Zilina, 2012)
The article deals with the calculation of reliability indicators of system dynamics, between the tunnel boring machine and the rock during the tunnel boring of the exploratory tunnel Branisko. The background deals with a design of a tunnel boring machine as a whole where the observed parts are rolling chisels in relation to the length of tunnel boring, as well as physical and technological properties of disintegrated rock.